2012
DOI: 10.5402/2012/691430
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin A2 Protein Overexpression Is Not Caused by Gene Amplification in Colon Cancer

Abstract: Increased expression of cyclin A2 protein has been detected in different types of cancers. However, its prognostic importance appears to differ between tumours. The significance and precise mechanisms behind cyclin A2 overexpression remain to be elucidated. We used real-time PCR to examine CCNA2 amplification in tumour cells isolated by laser microdissection and in total tumour tissue in colon cancer patients in which overexpression of cyclin A2 protein had been revealed by immunohistochemistry (n = 22 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Although tumors that showed cyclin A overexpression were larger, no difference proved to be statistically significant. In previous reports on different tumors, cyclin A overexpression demonstrated good correlation with tumor grade (Handa et al, 1999; Ito et al, 2002; Saarilahti et al, 2003; Sørby et al, 2012), but not with tumor size (Oda et al, 2003; Ha et al, 2012). There have been no results regarding cyclin A or any other cyclin expression in relation to size of WT published so far.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Although tumors that showed cyclin A overexpression were larger, no difference proved to be statistically significant. In previous reports on different tumors, cyclin A overexpression demonstrated good correlation with tumor grade (Handa et al, 1999; Ito et al, 2002; Saarilahti et al, 2003; Sørby et al, 2012), but not with tumor size (Oda et al, 2003; Ha et al, 2012). There have been no results regarding cyclin A or any other cyclin expression in relation to size of WT published so far.…”
Section: Discussionmentioning
confidence: 70%
“…In our study, about 34% WT showed cyclin A overexpression, defined as increased level of cyclin A comparing with normal kidney tissue. Cyclin A overexpression was found in different human tumors in adults (Aaltomaa et al, 1999; Poikonen et al, 2005; Sørby et al, 2012; Cyniak-Magierska et al, 2015), as well as in pediatric embryonal tumors (Moschovi et al, 2011) and in neuroblastoma tumor NI65 (Molenaar et al, 2003). In contrast, Wang et al (1996) reported decreased expression of cyclin A in colon cancer compared to normal colon mucosa in 63% cases.…”
Section: Discussionmentioning
confidence: 99%
“…To verify synthesis of microbial and human cDNA and to assess possible contaminating genomic DNA real-time PCR was performed using ABI Prism 7900HT Real Time PCR System (Applied Biosystems, Thermo Fisher Scientific, Waltham, MA, USA) and the software system SDS 2.4 (Applied Biosystems). The primers used for microbial 16S cDNA amplification were 357F and 926R [ 17 ], and for human cDNA amplification ACTB-F: 5′-GGT GTT TGT CTC TCT GAC TAG-3′, and ACTB-R: 5′-TGT CAC ACG AGC CAG TAT TAG-3′ [ 18 ]. The PCR amplifications were performed in triplicates using a 20 µl final reaction mixture containing 10 µl Power SYBR Green PCR Master mix (Applied Biosystems), 4 µl primer mix (5 µM), 4 µl NFW and 2 µl template.…”
Section: Methodsmentioning
confidence: 99%